VEGFR2 but not VEGFR3 governs integrity and remodeling of thyroid angiofollicular unit in normal state and during goitrogenesis. Issue 6 (24th April 2017) - Jang, Jeon Yeob; Choi, Sung Yong; Park, Intae; Park, Do Young; Choe, Kibaek; Kim, Pilhan; Kim, Young Keum; Lee, Byung‐Joo; Hirashima, Masanori; Kubota, Yoshiaki; Park, Jeong‐Won; Cheng, Sheue‐Yann; et al.
Abstract: Thyroid gland vasculature has a distinguishable characteristic of endothelial fenestrae, a critical component for proper molecular transport. However, the signaling pathway that critically governs the maintenance of thyroid vascular integrity, including endothelial fenestrae, is poorly understood. Here, we found profound and distinct expression of follicular epithelial VEGF‐A and vascular VEGFR2 that were precisely regulated by circulating thyrotropin, while there were no meaningful expression of angiopoietin–Tie2 system in the thyroid gland. Our genetic depletion experiments revealed that VEGFR2, but not VEGFR3, is indispensable for maintenance of thyroid vascular integrity. Notably, blockade of VEGF‐A or VEGFR2 not only abrogated vascular remodeling but also inhibited follicular hypertrophy, which led to the reduction of thyroid weights during goitrogenesis. Importantly, VEGFR2 blockade alone was sufficient to cause a reduction of endothelial fenestrae with decreases in thyrotropin‐responsive genes in goitrogen‐fed thyroids. Collectively, these findings establish follicular VEGF‐A–vascular VEGFR2 axis as a main regulator for thyrotropin‐dependent thyroid angiofollicular remodeling and goitrogenesis. Synopsis: The follicular VEGF‐A–vascular VEGFR2 axis regulates thyroid follicle integrity and is a key mediator of thyrotropin‐dependent angiofollicular remodeling and goitrogenesis. Follicular VEGF‐A and vascular VEGFR2 expression are precisely regulated by thyrotropin stimulation in the thyroid gland. Blockade of VEGF‐A or VEGFR2 induces thyroid vascular regression during the physiologic state and abrogates angiofollicular remodeling during goitrogenesis. Microvessel densities and their VEGFR2 expression are increased in thyroid glands of patients with Graves' disease. VEGFR2 inhibition reduces transcellular transport capacities of thyroid vasculatures and thyrotropin‐responsiveness of follicular cells, ultimately inhibiting goitrogenesis. Abstract : The follicular VEGF‐A–vascular VEGFR2 axis regulates thyroid follicle integrity and is a key mediator of thyrotropin‐dependent angiofollicular remodeling and goitrogenesis.